2019
DOI: 10.31557/apjcp.2019.20.2.519
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of LGR4 and Β-Catenin in Gastric Cancer and Normal Gastric Mucosa

Abstract: Background:We evaluated the immunoexpression of LGR4 and β-catenin in primary gastric carcinomas, lymph node metastases and histologically normal gastric mucosa in the surgical margins of gastric primary tumours. Methods:We performed a cross-sectional, observational study, based on 75 gastric carcinoma specimens from gastrectomies conducted at the hospital of the Federal University of Ceará, Brazil. The samples were analysed by tissue microarray and immunohistochemistry. Chi-square, Fisher’s exact test and Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…LGR4 acted as an essential positive factor for inducing skin tumorigenesis by activating MEK1/ERK1/2/AP-1 and Wnt/β-catenin pathways ( Xu et al, 2016 ). Conversely, Souza, S. M. et al detected that LGR4 was expressed in a larger number of cells in normal gastric mucosa than in primary gastric carcinomas and not specific to gastric cancer cells, predominantly affecting the expression of β-catenin in membrane-complex but rarely in nucleus, suggesting a controversial function of LGR4, and which was positively correlated with cell proliferation but inversely related to cancer progression ( Souza et al, 2019 ) ( Table 5 and Figure 4 ). Due to various carcinogenic factors, multiple cellular microenvironment and a variety of cell types, the complicated functions of LGR4 in carcinogenesis needed further exploration.…”
Section: Suggested Roles Of Lgr4 In Carcinomasmentioning
confidence: 96%
“…LGR4 acted as an essential positive factor for inducing skin tumorigenesis by activating MEK1/ERK1/2/AP-1 and Wnt/β-catenin pathways ( Xu et al, 2016 ). Conversely, Souza, S. M. et al detected that LGR4 was expressed in a larger number of cells in normal gastric mucosa than in primary gastric carcinomas and not specific to gastric cancer cells, predominantly affecting the expression of β-catenin in membrane-complex but rarely in nucleus, suggesting a controversial function of LGR4, and which was positively correlated with cell proliferation but inversely related to cancer progression ( Souza et al, 2019 ) ( Table 5 and Figure 4 ). Due to various carcinogenic factors, multiple cellular microenvironment and a variety of cell types, the complicated functions of LGR4 in carcinogenesis needed further exploration.…”
Section: Suggested Roles Of Lgr4 In Carcinomasmentioning
confidence: 96%
“…Some cells migrate upward and differentiate into surface mucous cells; some remain local or migrate downward and differentiate into other fundic gland cells. [12][13][14][15] The present study found that the occurrence of gastric mucosal atrophy due to Hp infection was mainly caused by the failure of stem cells in the proliferative region of the gastric mucosa to differentiate and migrate normally. Additionally, based on the results of this study, the formation process of gastric mucosal atrophy is proposed as follows via the observation of 197 cases with atrophic gastric mucosal lesions.…”
mentioning
confidence: 97%